2020
DOI: 10.1371/journal.pone.0244642
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its determinants in Ethiopia: A systematic review and meta-analysis

Abstract: Introduction Hypertension is a major public health problem globally and it is a leading cause of death and disability in developing countries. This review aims to estimate the pooled prevalence of hypertension and its determinants in Ethiopia. Methods A systematic literature search was conducted at the electronic databases (PubMed, Hinari, and Google Scholar) to locate potential studies. Heterogeneity between studies checked using Cochrane Q test statistics and I2 test statistics and small study effect were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 87 publications
20
46
2
Order By: Relevance
“…Besides, in a study conducted in South Africa, the spatial distribution of nutritional status among childhood period was non-random geographically [ 26 ]. Furthermore, a recent study conducted on the spatial distribution of iron-rich food consumption in Ethiopia showed that spatial clustering was consistent with this finding [ 27 ]. The observed geographical variation of poor consumption of foods rich in vitamin A across regions of Ethiopia might be due to the regional variation in dietary preference, low practice to complementary feeding, socioeconomic status, demographic factors such as pastoralist region, and seasonal differences for the consumption of fruits and vegetables [ 28 ].…”
Section: Discussionsupporting
confidence: 79%
“…Besides, in a study conducted in South Africa, the spatial distribution of nutritional status among childhood period was non-random geographically [ 26 ]. Furthermore, a recent study conducted on the spatial distribution of iron-rich food consumption in Ethiopia showed that spatial clustering was consistent with this finding [ 27 ]. The observed geographical variation of poor consumption of foods rich in vitamin A across regions of Ethiopia might be due to the regional variation in dietary preference, low practice to complementary feeding, socioeconomic status, demographic factors such as pastoralist region, and seasonal differences for the consumption of fruits and vegetables [ 28 ].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the likelihood of hypertension among participants who ever used alcohol was 3.25 times more likely as compared to those who never used alcohol. This was in agreement with those of studies conducted in Dabat HDSS(84), Dabat district and Gondar town (32), Gondar city (34), Addis Ababa(41), Jimma town(87), Wolega(85), Sidama Zone (64, 86), Bale Zone (93), and systematic review and metaanalysis conducted in Ethiopia (29). This nding was also in agreement with those of studies conducted in rural districts of Cameroon (57), Uganda(68), South India (59), and urban Varanasi (91) where individuals who used alcohol were found to be more hypertensive than who never used alcohol.…”
Section: Discussionsupporting
confidence: 91%
“…Hypertension affects over 20% of adult population in Ethiopia (29). Several community based studies have been conducted in urban settings of Ethiopia and showed high prevalence of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…8 Hypertension affects nearly 1 in 4 Ethiopian adults and becomes a major public health problem. 9 Literature showed that the pooled prevalence of hypertension was 21.8% 10 and ranged from 13.2% 11 in southwest Ethiopia to 31.9% in Dabat northwest Ethiopia. 12 Hypertension, if left untreated and uncontrolled, might lead to cardiovascular disease morbidity, disability, and mortality.…”
Section: Introductionmentioning
confidence: 99%